A cooperação como norma fundamental na formação democrática das decisões judiciais - Fernandes, Jorge Luiz Reis (2016)
The thesis aims to reveal the meaning of a cooperatively structured legal process, which involves in theory a substantive decision within a reasonable time that is fair and effective. The paper presents that the scope of this desideratum, to obtain an adequate decision, undergoes a process in which the parties are symmetrical in the proceedings, effectively influencing the decisions taken by the magistrate, who will only be isolated from the parties at the time of the ruling and not at the construction of the proceedings. It starts from a publicist ideal, from a democratic model of process forged through extensive dialogue between the parties and the magistrate, and the resulting dialecticism promotes a genuine contradictory, changing the design of the aphorisms mihi factum dabo tibi ius and iura novit curia, because everyone should contribute to the social peace, with no surprises. The collaboration between the parties brings duties for all parties with no exception, but the most important role belongs to the magistrate, which entails clarification duties, prevention, dialogue and aid. The parties serve diverse interests and contribute little, especially since there is a gap between them, which is exactly the reason of the litigation, including the right against self-incrimination principle. However, they cooperate with the duty of good faith. The study also faces another problem, which is the question of whether or not cooperation is a principle, not as predominant orientation, but as normative species. Finally, for the formation of a cooperative and democratic process, everyone should conduct the process as a working community